Dinamika Persaingan di Era Digital: Strategi Manajemen untuk Menghadapi Disrupsi Bagi Mahasiswa STIE Ganesha - Asep Surya Lesmana (FEB Universitas Maritim Semarang, 2023)
In the ever-evolving digital era, disruption challenges face Micro, Small, and Medium Enterprises (MSMEs), including STIE Ganesha students who are preparing to enter the business world. This research explores management strategies that can help MSMEs face disruption in the digital era. Using a qualitative approach, this research aims to identify disruption trends, challenges faced, and effective management strategies. The research was conducted over six months, involving in-depth interviews with MSME owners who have experienced digital disruption. Data analysis used a qualitative approach by formulating patterns of findings that emerged from the interviews. The results showed that the strategy of STIE Ganesha students in facing disruption is the adoption of MSME digital technology, understanding of data and analytics, continuous innovation, focus on customer experience, collaboration and partnerships, increasing cyber security, increasing human resource capacity, flexibility and adaptability of creative marketing understanding of business legal aspects. The implication of this research is to provide practical guidance for STIE Ganesha students who will later run or support MSMEs. Research limitations include limitations in the number of samples and focus on local cases.